The Effect Of Giving A Vibrator With A Cooler On Pain Level In Childhood With Venipuncture In Tidore Kepulauan Hospital - Abdullah, Fadila; Anwar, Nursanti (RSUP Dr. Kariadi, 2023)
BACKGROUND : Atraumatic care is therapeutic care that is carried out as part of an intervention to remove or suppress psychological or physical stress suffered by a child. The act of minimizing pain, stress and trauma to children when given at the time of blood collection is part of the principle of atraumatic care. One of the atraumatic actions that can be performed on children is the use of a vibrator with a cooler to minimize pain when stabbing a vein AIMS : to determine the effectiveness of giving a vibrator accompanied by a cold compress against pain in children when taking venous blood. METHODS : The design of this research is true experimental with a post-test only control group design. Researchers divided into 2 groups, namely the intervention and control groups were taken randomly. Then the researcher made a vibrator with a cooler that had been previously tested on 30 adults, then after being declared to have passed the ethical study it would be applied to children when taking venous blood, assessing children's pain using the FLACC instrument (face, legs, activity, cry and controllability). The study was conducted at the Tidore Islands Hospital. Data processing was carried out previously by testing the homogeneity and normality test, if normally distributed it will use the independent t-test to assess the difference in the average of the two groups, while if it is not normally distributed it will be tested with Mann-Whitney. RESULT : The results of this study indicate that the characteristics of respondents according to age are mostly 4 years old. In the control group the average age of children is 3.87 while in the intervention group the average age of children is 3.93. Most of the experience of having blood drawn in both groups had blood drawn before. Based on gender characteristics, most of the control and intervention groups were women. There are differences in pain scores in the control and intervention groups. The mean pain score in the intervention group was 3.13 and the mean pain score in the control group was 7.87. The results of statistical tests using Mann Whitney showed that there was a significant difference in pain during venipuncture in the intervention group and the control group (p=0.013). CONCLUSION : The results of the statistical test show that there was a significant difference in pain in the intervention group and the control group (p=0.013). The use of a cooling vibrator can be an alternative to reduce pain in children during venipuncture.